1969
DOI: 10.1002/macp.1969.021230127
|View full text |Cite
|
Sign up to set email alerts
|

Morphological studies on precipitated cellulose

Abstract: In connection with the problem of biosynthesis of cellulose, it is of fundamental importance to decide whether the crystal structure and morphological features of the native fibriles are also genetically determined through some kind of matrix mechanism, or are simply the end result of a spontaneous crystallization process.The recently reported observationl) that fibrils showing native structure (unit cell I) and morphology can precipitate spontaneously from dilute solutions of native cellulose seems to favor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…2,3 This result supports the concept of cellulose I microfibrils crystallization without the direct involvement of living cells. 4,5 Using A. xylinum, a bacterium that synthesizes a highly crystalline ribbon of cellulose I, Kai et al 3,6,7 and Haigler and coworkers. 8,9 have demonstrated that fluorescent brightening agents and direct dyes that bind to cellulose in vivo can separate glucan chain polymerization from microfibril crystallization.…”
Section: Introductionmentioning
confidence: 98%
“…2,3 This result supports the concept of cellulose I microfibrils crystallization without the direct involvement of living cells. 4,5 Using A. xylinum, a bacterium that synthesizes a highly crystalline ribbon of cellulose I, Kai et al 3,6,7 and Haigler and coworkers. 8,9 have demonstrated that fluorescent brightening agents and direct dyes that bind to cellulose in vivo can separate glucan chain polymerization from microfibril crystallization.…”
Section: Introductionmentioning
confidence: 98%
“…4-26). Fibrils with the lattice of cellulose I could be precipitated from cuoxam solution (Macchi, Palma 1969). Fibrils with the lattice of cellulose I could be precipitated from cuoxam solution (Macchi, Palma 1969).…”
Section: Crystallinity and The Size Of Crystallitesmentioning
confidence: 99%